Kajian Ayat Dalam Lambang PERSIS Makna dan Spirit Alquran Surat Ali Imran ayat 103 terhadap PERSIS - Fajar, Kamal Maulana (Ta'lim : Jurnal Multidisiplin Ilmu, 2024)
Indonesia is one of the countries with the largest Muslim populations in the world, making it easier to observe religious phenomena among Muslims. Persis represents one such phenomenon, illustrating how a Muslim lives out their faith with unity and guided by Q.S. Ali Imran:103. How did Persis emerge, and how do they interact with Q.S. Ali Imran:103. This research aims to uncover these phenomena: how Muslims, particularly those in Persis, emerge and engage in religious activities based on Q.S. Ali Imran:103. Using qualitative methods, it examines data gathered from literature and interviews. The study reveals how Q.S. Ali Imran:103 has provided spiritual inspiration to Persis members since its inception, guiding them through various challenges. It can be concluded that Q.S. Ali Imran:103, the motto since Persis' founding, is not just an identity but a source of collective enthusiasm and strategic direction in carrying out the mission of purifying Islam.